2020
DOI: 10.1002/jlb.4ma0520-708r
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional T cell response in convalescent patients two years after ZIKV infection

Abstract: Zika is an important emerging infectious disease in which the role of T cells remains elusive. This study aimed to evaluate the phenotype of multifunctional T cells in individuals 2 yr after exposure to Zika virus (ZIKV). We used a library of 671 synthetic peptides covering the whole polyprotein of ZIKV in pools corresponding to each viral protein (i.e., capsid, membrane precursor or prM, envelope, NS1 [nonstructural protein], NS2A + NS2B, NS3, NS4A + NS4B, and NS5) to stimulate PBMCs from individuals previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…They stimulated the PBMCs from these individuals with a wide range of synthetic peptides from the entire ZIKV polyprotein, divided into pools according to each of the viral protein's region. They showed that IFN-γ+ IL-17A+ and IL-17A+ IL-10+T cells could also produce TNF in response to stimulation with antigens of the capsid, prM, NS1 or NS3 regions [78].…”
Section: Discussionmentioning
confidence: 99%
“…They stimulated the PBMCs from these individuals with a wide range of synthetic peptides from the entire ZIKV polyprotein, divided into pools according to each of the viral protein's region. They showed that IFN-γ+ IL-17A+ and IL-17A+ IL-10+T cells could also produce TNF in response to stimulation with antigens of the capsid, prM, NS1 or NS3 regions [78].…”
Section: Discussionmentioning
confidence: 99%
“…Multifunctional properties were observed in ZIKV-specific T cells responding especially to prM, capsid, NS1, or, to a smaller extent, NS3 antigens. In addition, CD8+ T cells were more prone to a multifunctional phenotype than were CD4+ T cells [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models suggest that an effective immune response against ZIKV is driven by multifunctional CD4+ and CD8+ T cells [ 59 , 63 ]. We have found that ZIKV-specific T cells display a dominant multifunctional profile secreting multiple cytokines, especially IFNg, IL-17A, TNF and IL-10, simultaneously (quadruple-producing T cells) or its combinations [ 64 ] ( Figure 1 ). Interestingly, we observed that CD8+ T cells displayed higher frequencies of multifunctional lymphocytes when compared to CD4+ T cells [ 64 ].…”
Section: Immune Responsesmentioning
confidence: 99%
“…We have found that ZIKV-specific T cells display a dominant multifunctional profile secreting multiple cytokines, especially IFNg, IL-17A, TNF and IL-10, simultaneously (quadruple-producing T cells) or its combinations [ 64 ] ( Figure 1 ). Interestingly, we observed that CD8+ T cells displayed higher frequencies of multifunctional lymphocytes when compared to CD4+ T cells [ 64 ]. Indeed, multifunctional T cell responses and cellular immunity have been considered important mechanisms for host resistance against other flaviviruses like DENV [ 51 , 65 ] and immunity to YFV [ 66 , 67 , 68 ].…”
Section: Immune Responsesmentioning
confidence: 99%